2011
DOI: 10.1038/nn.2733
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the activity of neuronal populations in macaque primary visual cortex

Abstract: Visual function depends on the accuracy of signals carried by visual cortical neurons. Combining information across neurons should improve this accuracy because single neuron activity is variable. We examined the reliability of information inferred from populations of simultaneously recorded neurons in macaque primary visual cortex. We considered a decoding framework that computes the likelihood of visual stimuli from a pattern of population activity by linearly combining neuronal responses, and tested this fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
289
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(319 citation statements)
references
References 48 publications
(108 reference statements)
28
289
2
Order By: Relevance
“…Reports of the effects of ensemble r sc structure on information content vary significantly in sign and magnitude (19,22,24,27,42,48,49); our results can help reconcile these disparate accounts. For example, previous studies that applied decoding techniques to simultaneously recorded ensembles found that removing the r sc structure decreased decoding accuracy for grating orientation (48) and remembered location (49) whereas another study reported a positive effect of pairwise r sc on information coding (32).…”
Section: Discussionmentioning
confidence: 53%
“…Reports of the effects of ensemble r sc structure on information content vary significantly in sign and magnitude (19,22,24,27,42,48,49); our results can help reconcile these disparate accounts. For example, previous studies that applied decoding techniques to simultaneously recorded ensembles found that removing the r sc structure decreased decoding accuracy for grating orientation (48) and remembered location (49) whereas another study reported a positive effect of pairwise r sc on information coding (32).…”
Section: Discussionmentioning
confidence: 53%
“…4 and 5 are only satisfied when the distribution over either r A or r B given s takes the form pðr j sÞ ∝ ϕðrÞexpðhðsÞ · rÞ, where h(s) is a kernel related to the tuning curves and covariance matrix of the neural responses. Remarkably, this family of distributions, known as the exponential family with linear sufficient statistics, provides a very close approximation to the variability observed in vivo (22,38).…”
Section: Resultsmentioning
confidence: 88%
“…There is mounting evidence that understanding of information encoding in brain requires studying the correlation (noise correlation or Rsc; cross-correlations or CCG) between neurons (Perkel et al 1967;Alloway and Roy 2002;Bach and Kruger 1986;Zohary et al 1994;Averbeck and Lee 2003;Barthó et al 2004;Uhlhaas et al 2009;Cohen and Kohn 2011;Graf et al 2011;Cotton et al 2013;Cossell et al 2015).…”
Section: Introductionmentioning
confidence: 99%